Socio-Economic Impact Of Integrated Pest Management Field School Implementation On Coffee Farmers In Panditan Village - Muqtafiah Muqtafiah; Luchman Hakim; Aminudin Afandhi (JURNAL SERAMBI ILMU, 2022)
Integrated Pest Management Field School (IPM-FS) is an extension method that is still being applied in Indonesia. IPM-FS is considered still relevant to be applied in Indonesia. However, farmers still have obstacles that cause farmers so that to not fully apply the knowledge obtained from the Integrated Pest Control Field School. This research was conducted in Panditan Village, Lumbang District, Pasuruan. The method used is descriptive qualitative with the Process Tracing approach. Collecting data through observation, interviews, and documentation. The results showed that farmers benefited from the Integrated Pest Management Field School (IPM-FS), namely increasing farmer knowledge, changing farmer perceptions and behavior, and increasing coffee productivity. Constraints experienced by farmers are related to technology in the harvest process, causing farmers to still pick coffee as a whole without considering the color of the coffee beans between red, green, and yellow. The absence of a specific price difference between coffee with the implementation of IPM and non-IPM is also the background for farmers to pick coffee indiscriminately.